Frequency of Fatty Liver Changes on Ultrasound Abdomen in Non Diabetic Young Patients Having Chronic Right Hypochondrium Pain - Syed Anees Ahmed Gardezi, Najmusaqib Khan Niazi, Syed Haider Tirmizi, Iffat Rafique, Rabia Sadiq, Muneeb Ur Rehman, Talha Laique, (Pakistan Journal of Medical & Health Sciences, 2022)
With a prevalence of around 20 – 30% in world population, Fatty liver is becoming the most commonly occurring ailment. Aims: To check the frequency of fatty liver changes on ultrasound abdomen in non diabetic young patients presenting with chronic right hypochondrium pain of more than two weeks duration. Study Design: Cross-sectional study. Methodology: Patients (n=375) with an age range of 18 to 50 years presenting to the OPD with complaint of chronic right hypochondrium pain of more than 2 weeks duration were included into the study. Demographic details, Total serum cholesterol mg/dl, triglycerides and LFTs (ALT, AST U/L) were recorded. Patients were sent for ultrasound abdomen for confirmatory diagnosis and findings trained were recorded. All this information was recorded on Performa. Statistical analysis: Data was analyzed using SPSS version 26. Results were presented as frequency and percentage. Age was presented as mean± SD. Results: Out of total 375 patients 175 (45.6%) were male and 200 (52.1%) were female. Mean age of the patients was 32.65 ± 6.94 years. 56.5% (n=217) had fatty liver changes on ultrasound. 143 (65.8%) patients had grade I fatty changes, 58 (26.7%) had grade II and 16 (7.4%) had grade III liver disease. Conclusion: It was concluded that frequency of fatty liver changes detected on ultrasound was high in non diabetic young patients. Liver enzymes (especially ALT) showed an increasing trend as the disease severity increased on ultrasound.